The effectiveness of clinical education models for undergraduate nursing programs: A systematic review. (March 2018) - Jayasekara, Rasika; Smith, Colleen; Hall, Cath; Rankin, Elaine; Smith, Morgan; Visvanathan, Vicky; Friebe, Terry-Renette
Abstract: Clinical nurse education is a major part of all undergraduate programs preparing nurses for competent professional practice. While research mostly evaluated specific clinical education models, few studies compared different type of models and limited attention has been given to the effect on student learning outcomes. This systematic review aimed to examine the effectiveness of clinical education models for undergraduate nursing programs. This systematic review utilised the Joanna Briggs Institute systematic review approach (JBI, 2014). A web-based literature search was conducted to identify research studies published from 2002 to 2015 using a three-step search strategy. All selected papers were assessed by at least two independent reviewers for inclusion criteria, methodological validity, and data extraction in the review. This systematic review included nine studies including two pre-post-test studies with a control group totalling 1893 participants including 1286 nursing students. The evidence regarding the effectiveness of clinical education models for undergraduate nursing programs is notably weak; however this review found limited evidence that the clinical facilitator model is preferable to the preceptor model and the Clinical Education Unit (CEU) model provided greater engagement and an enhanced learning environment compared with the standard facilitation model. Highlights: Clinical nurse education is a major part of all undergraduate nursing programs. The evidence of clinical education models for nursing programs is notably weak. The clinical facilitator model is preferable to the preceptor model. Clinical Education Unit (CEU) model is preferable to standard facilitation model.